2022
DOI: 10.1126/science.abn8343
|View full text |Cite
|
Sign up to set email alerts
|

Concise syntheses of GB22, GB13, and himgaline by cross-coupling and complete reduction

Abstract: Neuroactive metabolites from the bark of Galbulimima belgraveana occur in variable distributions among trees and are not easily accessible through chemical synthesis because of elaborate bond networks and dense stereochemistry. Previous syntheses of complex congeners such as himgaline have relied on iterative, stepwise installation of multiple methine stereocenters. We decreased the synthetic burden of himgaline chemical space to nearly one-third of the prior best (7 to 9 versus 19 to 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 44 publications
0
17
0
2
Order By: Relevance
“…Analysis of the chemical space that is accessible by specific reactions and subsequent collation with the known product chemical space and the accessible chemical space of other reactions can provide important information about the synthetic potential of chemical methodologies and guide the development of new reactions. The recently developed PARSE (Prospective Analysis of Reaction Scope) tool enables facile mapping of the accessible chemical space using molecular weight (MW), molecular complexity ( C m ), and fraction of sp 3 carbon atoms (Fsp 3 ) as descriptors and subsequent comparison between different reactions and with the total chemical space of expected reaction products . Importantly, while the same chemical space can potentially be accessed by a sequence of several reactions, PARSE studies are limited to the comparison of direct transformations, which is in line with the main goal of such studies, that is, to inform and guide the development of more efficient synthetic methodologies for direct functional group interconversions .…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the chemical space that is accessible by specific reactions and subsequent collation with the known product chemical space and the accessible chemical space of other reactions can provide important information about the synthetic potential of chemical methodologies and guide the development of new reactions. The recently developed PARSE (Prospective Analysis of Reaction Scope) tool enables facile mapping of the accessible chemical space using molecular weight (MW), molecular complexity ( C m ), and fraction of sp 3 carbon atoms (Fsp 3 ) as descriptors and subsequent comparison between different reactions and with the total chemical space of expected reaction products . Importantly, while the same chemical space can potentially be accessed by a sequence of several reactions, PARSE studies are limited to the comparison of direct transformations, which is in line with the main goal of such studies, that is, to inform and guide the development of more efficient synthetic methodologies for direct functional group interconversions .…”
Section: Resultsmentioning
confidence: 99%
“…[18] To enable the visualization of the chemical space, the analysis was performed on representative samples (0.25 % of the Pubchem-derived datasets for each class of compounds, i.e., carboxylic acids, sulfinates, and sulfoxides), resulting in 805 known sulfoxides and 196749 decarboxylative sulfinylationaccessible sulfoxides (from the representative datasets of 7287 carboxylic acids and 27 sulfinates). The chemical space of the known and decarboxylative sulfinylation-accessible sulfoxides was then compared using molecular weight (MW), molecular complexity (C m ), [19] and fraction of sp 3 carbon atoms (Fsp 3 ) [20] as descriptors [21] that were selected based on the importance of the molecule size, as well as structural and functional group content, and the threedimensional molecular shape for applications in drug discovery, materials science, and organic synthesis. A comparison of the representative set of currently available sulfoxides with the structures of sulfoxides that can become accessible by the direct decarboxylative sulfinylation revealed that the decarboxylative sulfinylation-accessible sulfoxides have a significantly broader distribution with respect to molecular weight (MW), molecular complexity (C m ), and fraction of sp 3 carbon atoms (Fsp 3 ) (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Further modifications of 112 led to the common scaffold 113 in 47% yield, which could be readily transformed to several crinipellin natural products by chemoselective redox reactions. Divergent total synthesis of Galbulimima alkaloids (Shenvi 2022) [62]: Members of the Galbulimima alkaloids extracted from rainforest canopy trees were found to possess neuroactive properties, such as antagonistic activity at muscarinic receptors [63], psychotropic activity, and antiplasmodic activity [64]. Their structural diversity, consisting of different connectivities between piperidine and decalin domains, is especially difficult to be divergently accessed.…”
Section: Divergent Total Synthesis Of Crinipellinsmentioning
confidence: 99%